On Exactly Solvable Lattice Models and Their Mathematical Properties - Poghosyan, Vahagn S. (Mathematical Problems of Computer Science, 2025)
This paper provides a comprehensive review of our previously obtained results on exactly solvable lattice models, with a primary focus on the Abelian sandpile model, dimer model, loop-erased random walks and their connections to the enumeration of spanning trees.